Association between dental prosthesis and periodontal disease in a rural Brazilian community - Suzely Adas Saliba Moimaz; Nemre Adas Saliba; Orlando Saliba; Lívia Guimarães Zina; Márcio Rogério Curtis Bolonhez (Brazilian Journal of Oral Sciences, 2016)
The aim of this study was to describe the periodontal conditions and to analyze the association between the wearing of fixed/removable partial dentures and periodontal disease in a representative adult rural population in southeast Brazil. Cross-sectional study of a representative sample comprising 200 individual aged 34-44 years. Data were collected by clinical examinations in accordance with the World Health Organization Basic Methods Criteria, which included the Community Periodontal Index and dental prosthesis exam. A descriptive analysis and the chi-square statistic were performed. In total, 40.5% of the individuals wore partial denture and 59.5% were non-users of denture. The prevalence of periodontal disease was 100%. The subjects scored either calculus (44.5%) or shallow pockets (47%), and only a small proportion was recorded as having deep pockets (8.5%). All denture wearer displayed periodontal problem in the sextant where the denture were recorded. The statistical analysis indicated that wearing partial dentures was found to be associated with considerable periodontal disease (X2 = 10.75; p=0.0014). The periodontal condition of the study population can be considered unsatisfactory. The wearing of partial dental prosthesis was associated with periodontal disease, and a significant percentage of cases might have been prevented if plaque control interventions had been implemented